A cooperação no CPC-2015: colaboração, comparticipação ou cooperação para o processo? - Pimenta, Henrique de Souza (2018)
The research is dedicated to the subject of procedural cooperation, in order to examine which procedural subjects are bound by cooperative duties from the cooperative process model inaugurated by the Procedure Civil Code of 2015. It identifies, from a historical perspective, the existence of three models of procedural organization: adversarial, inquisitorial and cooperative. The adversarial model is related to the Liberal State and its central characteristics are the protagonism of the parties in the conduct of the process and the relatively passive position of the judge during the procedural. The inquisitorial model corresponds to the Social State and is marked by the presence of the judge as the main character of the process with a view to finding the "real truth". From its turn, the cooperative model is compatible with the Constitutional Democratic State and organizes the process around a "work community", in which all the procedural subjects contribute, from a dialogic environment, to the formation of the decision of judicial process of fair, timely and effective merit. It notes that the cooperative model find its foundation from the principle of cooperation, which is understood as a principle endowed with normativity to impose a state of affairs, so that, all conduct contrary to the promotion of a cooperative process environment will be considered illegal. It notes that cooperative duties derive from the principle of good faith and imply cooperative behavior for all procedural subjects. It states that the objective of the contemporary process is to safeguard rights in a fair, adequate, timely and compatible manner to fundamental rights, so that all procedural subjects, without exception, must observe cooperative duties. It verifies that cooperative duties are linked to the counterfactual function of the legal phenomenon, so that counterintuitive behaviors will be imposed on procedural subjects, so that all procedural subjects cooperate for the process. It notes that non-compliance with cooperative duties generates sanctions expressly established by law, as well as having the potential to entail a number of procedural disadvantages, such as a default judgment, the preclusion of untimely arguments, a judgment of merit on the grounds of insufficiency of evidence.